Financing Student Migration: Evidence for a Commitment Problem - Romuald Méango (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2014)
This paper develops and tests a model of profit-sharing arrangement over returns to a student migration investment. Taking advantage of a unique dataset on Cameroonian students, I find evidence of non-commitment bargaining between student, parents and an outside helper. The commitment problem arises because the coalition of parents and student has strong incentives not to abide by the outcome of the ex ante negotiation with the helper. This finding suggests some inefficiency of the decision process, in that students from credit-constrained families might not benefit from the support of a helper, even though the returns to their migration can be significant.
Keywords: C71; I25; J61; 330; Student migration; bargaining; commitment